The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/agronomy9050260
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biochar and Solid Digestate on Rose-Scented Geranium (Pelargonium graveolens L’Hér.) Productivity and Essential Oil Quality

Abstract: In recent years, biochar has generated global interest in the areas of sustainable agriculture and climate adaptation. The main positive effects of biochar were observed to be the most remarkable when nutrient-rich feedstock was used as the initial pyrolysis material (i.e., anaerobic digestate). In this study, the influence of solid anaerobic digestate and biochar that was produced by the slow pyrolysis of solid digestate was evaluated by comparing the differences in the crop growth performances of Pelargonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…Biochar is produced with dry pyrolysis of the organic matter, in which plant or animal-based organic materials are subjected to high temperatures (450 to 600 • C), under hypoxia or anoxia environment [1,2], whereas lower temperature (300 • C) have been reported for biochar production [3]. The initial organic material for biochar production is mainly wastes coming from intensive sectors, such as forest residues and wood industries, agriculture and food, and greatly contribute to the environmental management and recycling, reducing the greenhouse gas (GHG) emission and increasing carbon sequestration [4][5][6][7]. The use of biochar in the agriculture sector as an alternative container growing media adds value to the bioenergy business process [8].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is produced with dry pyrolysis of the organic matter, in which plant or animal-based organic materials are subjected to high temperatures (450 to 600 • C), under hypoxia or anoxia environment [1,2], whereas lower temperature (300 • C) have been reported for biochar production [3]. The initial organic material for biochar production is mainly wastes coming from intensive sectors, such as forest residues and wood industries, agriculture and food, and greatly contribute to the environmental management and recycling, reducing the greenhouse gas (GHG) emission and increasing carbon sequestration [4][5][6][7]. The use of biochar in the agriculture sector as an alternative container growing media adds value to the bioenergy business process [8].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar production is a process of dry pyrolysis of organic matter, whereby plant or animal-based organic materials are treated under high temperatures ranging from 450 to 600 • C, under the absence of oxygen or low oxygen conditions [1,2], while lower temperature (300 • C) for biochar production has been reported [3]. Primary material for biochar production is mainly wastes derived from intensive sectors such as agriculture, food, forest residues and wood industries with significant contribution to environmental management and recycling, decreasing the greenhouse gas (GHG) emission and sequester carbon [4][5][6][7]. Biochar (i.e., 70%) use in agriculture as an alternative container substrate adds value to the bioenergy process with significant reduction (up to 54%) of the cost for the use of peat-based substrates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Uzoma et al [46] reported favorable use of cow-manure biochar in first-year maize cultivation, probably due to the high ion concentrations and relatively quick release compared to that of other plant-derived biochar [20]. This trend was also confirmed by foliar nutrient content, where a high microelement presence in biochar caused greater leaf accumulation and plant development both in maize and geranium for essential-oil (Pelargonium graveolens) cultivation [12,47]. Concerning application rate, the authors reported positive maize growth using biochar up to 2%-3 % w/w [13,48].…”
Section: Amendment Influence On Maize Growthmentioning
confidence: 88%
“…In particular, the authors suggested that biochar produced from nutrient-rich feedstock such as digestate possesses higher nutrient contents than that of biochar obtained from nutrient-poor feedstock (i.e., wood residues), which determines lower soil benefits due to lower mineralization rates [9,10]. From a plant-growth standpoint, open-field or pot biochar application exerts highly variable results, reporting a positive, minimal, or negative influence [9,11,12]. Contrasting results for different biochars were observed in sandy-loam soils.…”
Section: Introductionmentioning
confidence: 99%